2004
DOI: 10.1021/ac034920m
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite-Containing Spherical Silica Nanoparticles for Biocatalysis and Bioseparations

Abstract: The simultaneous entrapment of biological macromolecules and nanostructured silica-coated magnetite in sol-gel materials using a reverse-micelle technique leads to a bioactive, mechanically stable, nanometer-sized, and magnetically separable particles. These spherical particles have a typical diameter of 53 +/- 4 nm, a large surface area of 330 m(2)/g, an average pore diameter of 1.5 nm, a total pore volume of 1.427 cm(3)/g and a saturated magnetization (M(S)) of 3.2 emu/g. Peroxidase entrapped in these partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
226
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(237 citation statements)
references
References 36 publications
5
226
0
6
Order By: Relevance
“…The saturation moment per unit mass, M s , for SPIO-Au nanoshells was 3.5 emu/g at 20 kOe, which was about 5.9% of the M s for SPIO. This value for SPIO-Au is in accordance with previously reported data for silica-magnetite nanoparticles 20 . These data indicated that SPIO-Au nanoshells exhibit superparamagnetic characteristics.…”
Section: Magnetic Property Of Spio-au Nanoshellssupporting
confidence: 93%
“…The saturation moment per unit mass, M s , for SPIO-Au nanoshells was 3.5 emu/g at 20 kOe, which was about 5.9% of the M s for SPIO. This value for SPIO-Au is in accordance with previously reported data for silica-magnetite nanoparticles 20 . These data indicated that SPIO-Au nanoshells exhibit superparamagnetic characteristics.…”
Section: Magnetic Property Of Spio-au Nanoshellssupporting
confidence: 93%
“…These materials have been used in various scientific fields such as biotechnology, engineering, biomedical, environmental, and material science (1)(2)(3)(4). Solidphase extraction (SPE) is a routine extraction method for determining trace level contaminants in environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…Among them SPE is the most popular one in environmental analysis for its high extraction efficiency, low consumption of organic solvents and easy operation. Nanomaterials, which possess nanosized diameter and large surface area, are being applied in numerous scientific fields [1][2][3][4]. In this regard many research groups have developed various types of nanosized SPE sorbents [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%